1998
DOI: 10.1099/00207713-48-1-47
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic characterization and proposal of a new pigmented species to the genus Prevotella: Prevotella pallens sp. nov.

Abstract: Complete 163 rRNA gene sequences of three representative strains of anaerobic, Gram-negative, pigmented, moderately saccharolytic, indolepositive bacteria isolated from the oral cavity of humans were determined. According to comparative analyses of the rRNA sequence data, this organism represents a previously unknown species within the genus Prevotella. In addition, 22 representative strains and 21 reference strains (including 11 Prevotella intermedia and 10 Prevotella nigrescens strains) were subjected to mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…The description is as given by Könönen et al (1998) with the following addition. The genomic G+C content of the type strain is 37.4%.…”
Section: Discussionmentioning
confidence: 99%
“…The description is as given by Könönen et al (1998) with the following addition. The genomic G+C content of the type strain is 37.4%.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, at the species level, we found the relative abundance of Prevotella_pallens _ATCC_700821 was significantly decreased after 6‐month Invisalign orthodontic treatment (Group P) compared with that in Group B. Prevotella pallens , included in Prevotella intermedia group, is both biochemically and phylogenetically related to Prevotella intermedia and Prevotella nigrescens (Könönen, Eerola, & Frandsen, ). Könönen found that Prevotella pallens was common in oral findings from early childhood (Könönen et al, ).…”
Section: Discussionmentioning
confidence: 94%
“…JF122, Pseudomonas gessardii strain LZ‐E and Pseudomonas taiwanensis would be a potential applicant for chromium (Cr) remediation (Huang et al ., ; Majumder et al ., ; Zhou and Chen, ). Prevotella is a genus of Gram‐negative bacteria, which is closely related to various infections as introduced above (Könönen et al ., ). No studies have shown that Prevotella contributes to heavy metal speciation changes during composting.…”
Section: Discussionmentioning
confidence: 99%